KOMPOSISI JENIS PIGMEN ALGA HIJAU, YANG DIPEROLEH DARI PERAIRAN BOLOK KABUPATEN KUPANG - Kase, Alfred G.O (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Macroalgae live on the bottom of the waters where sunlight can still penetrate like land plants. Like macro algae in general, green algae have chlorophyll or other accessory pigments that are used for photosynthesis. This color composition is used to classify the types of macroalgae. The purpose of this study was to determine the composition of the types of pigments contained in green algae. This research was conducted in September - November 2021 in Bolok Marine Waters, Kupang Regency. The identification process of algae species and pigment extraction was carried out at the Biology Laboratory of Artha Wacana Christian University Kupang, Thin Layer Chromatography (TLC) and Spectrophotometric Methods were used to identify pigment types. The results of the collection found three species of green algae: Ulva lactuca, Ulva reticulata, and Halimeda opuntia, these three types of algae were found in the intertidal zone which is still influenced by tides. Thin Layer Chromatography results for these three green algae obtained 4 - 5 fractions with a range of Retention Factor (Rf) value 0.2 – 1.0. The Rf value of 1 in the first fraction was identified as b-carotene pigment, the Rf value of 0.6 and 0.5 in fractions 2 and 3 was an indicator of chlorophyll pigment, the gray Rf value of 0.4 is a type of pheophytin pigment, while the Rf value of 0 The yellow ,3 and 0.2 are indicators of the type of lutein pigment (xanthophyll).